2002
DOI: 10.1007/s001980200055
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Disequilibrium Test for Hand Bone Mineral Density and 11q12-13 Chromosomal Segment

Abstract: The main aim of the present study was to test the hypothesis that the bone mineral density (BMD) assessed from radiographs of the hand phalanges in a random sample of ethnically homogeneous pedigrees is linked to the 11q12-13 chromosomal segment. The data for the study were gathered from 574 Chuvasha individuals belonging to two- and three-generation pedigrees who live in small villages in the Bashkortostan autonomy, Russia. Preliminary statistical-genetic analysis of the BMD in the pedigrees studied showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Previous studies have provided substantial evidence in support of linkage to chromosome 11q12-23 [15][16][17][18][20][21][22] . The multiple linkages within this broad region could suggest that more than one osteoporosis susceptibility gene resides in this region.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous studies have provided substantial evidence in support of linkage to chromosome 11q12-23 [15][16][17][18][20][21][22] . The multiple linkages within this broad region could suggest that more than one osteoporosis susceptibility gene resides in this region.…”
Section: Discussionmentioning
confidence: 95%
“…One is located on chromosome 11q13-21 between D11S4162 and D11S4175, which affect BMD variation at FN, trochanter, and total hip in women, suggesting pleiotropic effects of this gene on hip BMD. Livshits et al [22] suggested the possible existence of two genetic sources in the chromosome 11q. One is located between the markers D11S1313 and DD11S1765, the other between D11S1983 and D11S1314.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, mice with targeted disruption of LRP5 have a deficit in bone formation and sustain fractures (Kato et al, 2002), whereas transgenic mice carrying the LRP5 gain-offunction mutation (G171V) develop increased bone mass and strength (Babij et al, 2003). Most importantly, a QTL for bone mineral density in the general population was mapped at 11q12-13, the LRP5 locus (Carn et al, 2002;Koller et al, 1998;Livshits et al, 2002).…”
Section: Ldl Receptor-related Protein 5 Gene Polymorphismsmentioning
confidence: 98%
“…In the general population a QTL for BMD [59][60][61] and stature [62,63] has been mapped to chromosome 11q12-13, where LRP5 is also located. Mice with targeted disruption of LRP5 have a deficit in bone formation and sustain spontaneous fractures [64]; and LRP5 has been shown to encode a transmembrane protein that mediates the Wnt/beta-catenin signaling pathway, that controls osteoblastic activity and bone formation [65,66].…”
Section: Low-density Lipoprotein Receptor-related Proteinmentioning
confidence: 99%